2018
DOI: 10.1111/jonm.12726
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ psychological empowerment: An integrative approach

Abstract: Aim To investigate the role of psychological empowerment as a mediator between authentic leadership and organisational citizenship behaviours (OCB), tardiness, absenteeism and intent to leave. Background Despite the extensive literature on predictors and outcomes of psychological empowerment, there is a lack of studies on the nursing profession using an integrative model, simultaneously focusing on the effects of authentic leadership and psychological empowerment on OCB, and time‐related misbehaviours. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…These ndings suggest that the work environment had a direct positive effect on midwives' clinical decision-making and could have an indirect positive in uence through psychological empowerment. Many researchers validated psychological empowerment as a mediator of work engagement, quality of care, career satisfaction and propensity to leave [50,58,59]. However, few studies have explored the role of psychological empowerment in the relationship between the work environment and clinical decision-making.…”
Section: Work Environment Positively Predicted Clinical Decision-maki...mentioning
confidence: 99%
“…These ndings suggest that the work environment had a direct positive effect on midwives' clinical decision-making and could have an indirect positive in uence through psychological empowerment. Many researchers validated psychological empowerment as a mediator of work engagement, quality of care, career satisfaction and propensity to leave [50,58,59]. However, few studies have explored the role of psychological empowerment in the relationship between the work environment and clinical decision-making.…”
Section: Work Environment Positively Predicted Clinical Decision-maki...mentioning
confidence: 99%
“…When analyzing nursing productivity in a challenging situation (such as pandemic disease), nurses' critical thinking, psychological status, and workplace support should be considered as key factors. Studies have demonstrated that empowered nurses more effectively complete their work, display higher organizational productivity, and display more favorable performance in nursing practice [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…In Nursing, psychological empowerment involves the perception of the professional about the valorization of their work and their contributions to contribute to the care processes, which leads to a feeling of competence and freedom. Thus, structural empowerment leads to nurses' psychological empowerment (6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the empowerment of nurses contributes to greater professional satisfaction, decreased burnout rates, and increased autonomy and organizational commitment. In addition, it positively impacts patient safety and quality of care in the health services (3)(4)(6)(7)(8) . As a result, it is necessary for the managers to be attentive to their organizational practices, since just ensuring the quality of the technical aspects of processes or services is no longer sufficient to maintain the efficiency of organizations, and it is also necessary to invest in the involved people (9) .…”
Section: Introductionmentioning
confidence: 99%